Characteristic and Knowledge among Treatment Supporter of Children Patients with Tuberculosis at Lung Clinic Bandung October–November 2012 - Kamelia Utami Suhada; Sri Yusnita Irda Sari; Diah Asri Wulandari; Elsa Pudji Setiawati (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Children are the most vulnerable to get TB infection and infected by adult patients. One of the components of Directly Observed Treatment Short Course (DOTS) is direct observation by treatment supporter who has important role in the success of TB’s treatment. The aim of this study was to identify the characteristics and knowledge among treatment supporter of children patients with TB at Lung Clinic Bandung.Methods: A descriptive study was conducted in October-November 2012 to 96 treatment supporters of child patients who were diagnosed with TB, either new or old cases. They were selected by consecutive sampling at Lung Clinic Bandung. Validated questionnaire with 14 questions was administered. The percentage of the correct answers was categorized as good, moderate, and poor. The Characteristic variables included age, sex, education, occupation, relation with the patients, living at the same house, presence of other TB patients, and counseling given by providers. Data was analyzed using frequency distribution.Result: Most of the respondents were 21-30 years old (42.7%), female (84.4%), elementary school graduate (33.3%), unemployed (69.8 %), mother of the child, living in the same house, had other TB patients, and had received counseling by providers at Lung Clinic. The knowledge about TB among the respondents was moderate (56.3%). The respondents who had good knowledge had underwent the counseling session.Conclusions: The knowledge of the respondents was moderate. Further study on the relationship between the level of knowledge of treatment supporter and the adherence of TB treatment should be conducted. [AMJ.2015;2(1):167–71]